Investigating the Predictive Value of Neutrophil to Lymphocyte Ratio on Radiation Therapy Outcomes: A Cohort Study - Muniba Alim; Shamila Alim; Shahid Siddiqui; Md Asif Khan (Journal of Clinical and Diagnostic Research)
Introduction: The gold standard in the management of locally advanced cervical cancer is definitive chemoradiation followed by brachytherapy. Nonetheless, the interdependence of radiation response and immune balance in cancers is debatable. Inflammation markers such as C-Reactive Protein (CRP) and Pro-B-type Natriuretic Peptide (Pro-BNP) have established prognostic value in cancers, but the Neutrophil-Lymphocyte Ratio (NLR) is gaining prominence due to its easy accessibility and strong predictive role in malignancies such as lung, pancreatic and gastric cancers. Aim: To study NLR as a predictor of clinical response to radiation in cervical cancer. Materials and Methods: This cohort study assessed 60 women from a tertiary cancer hospital in Western Uttar Pradesh, catering to many districts in North India, between August 2017 and July 2019. The routine blood investigations during assessment at baseline and NLR were obtained. Pelvic chemoradiation of 50 Gy in 25 fractions was administered over 5 weeks with weekly concomitant cisplatin at 35 mg/m². Tumour response was evaluated and statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) version 23.0 to find the association between NLR and Complete Response (CR). Results: Clinical CR was noted in 44 (73.3%) of participants. In the CR group, 10 (22.7%) had baseline haemoglobin levels below 13 g/dL compared to 13 (81.25%) in the Partial Response (PR) group. The majority of patients (39/44) with CRs were noted at NLR levels below 2.9. When the NLR (cut-off 2.9) and response (Complete and PR; CR and PR) were evaluated, the p-value was reported as 0.06, which, although not statistically significant, is encouraging for further investigation towards consensus. Conclusion: These observations suggest that inflammation appreciably influences the intrinsic tumour characteristics in patients with cervical cancer. Hence, the utility of NLR as a marker to categorise the risk of recurrence in patients with cervical cancer presents an intriguing concern for the future.